Unmasking pustular psoriasis subsequent to COVID-19 - Mohseni Afshar, Zeinab; Miladi, Ronak; Janbakhsh, Alireza; Babazadeh, Arefeh; Aryanian, Zeinab; Ebrahimpour, Soheil (Journal of Pakistan Association of Dermatologists, 2022)
The various cutaneous manifestations have recently appeared within context of 2019 novel coronavirus diseases (COVID-19). Currently, outbreaks of psoriasis were reported during COVID-19. We reported a case of a 32-year-old woman with COVID-19 who presented with pustular psoriasis. She was treated with oral prednisolone, hydroxyzine and topical clobetasol. The two-week follow-up revealed that her lesions were desquamating and that she was in a favorable situation. The current report will highlight specific skin manifestations of COVID-19, allowing clinicians to further confirm our suspicions.